Longer photoperiods through range shifts and artificial light lead to a destabilizing increase in host–parasitoid interaction strength. Issue 11 (18th September 2020) - Kehoe, Rachel; Sanders, Dirk; Cruse, Dave; Silk, Matthew; Gaston, Kevin J.; Bridle, Jon R.; van Veen, Frank
Abstract: Many organisms are experiencing changing daily light regimes due to latitudinal range shifts driven by climate change and increased artificial light at night (ALAN). Activity patterns are often driven by light cycles, which will have important consequences for species interactions. We tested whether longer photoperiods lead to higher parasitism rates by a day‐active parasitoid on its host using a laboratory experiment in which we independently varied daylength and the presence of ALAN. We then tested whether reduced nighttime temperature tempers the effect of ALAN. We found that parasitism rate increased with daylength, with ALAN intensifying this effect only when the temperature was not reduced at night. The impact of ALAN was more pronounced under short daylength. Increased parasitoid activity was not compensated for by reduced life span, indicating that increased daylength leads to an increase in total parasitism effects on fitness. To test the significance of increased parasitism rate for population dynamics, we developed a host–parasitoid model. The results of the model predicted an increase in time‐to‐equilibrium with increased daylength and, crucially, a threshold daylength above which interactions are unstable, leading to local extinctions. Here we demonstrate that ALAN impact interacts with daylength and temperature by changing the interaction strength between a common day‐active consumer species and its host in a predictable way. Our results further suggest that range expansion or ALAN‐induced changes in light regimes experienced by insects and their natural enemies will result in unstable dynamics beyond key tipping points in daylength. Abstract : Through a combination of experiments and modelling we show that changes in light regime though species' range expansion and artificial light at night destabilize a host–parasitoid interaction. This effect is caused by increasing the parasitoid's attack rate. These results have strong implications for food web stability and pest outbreaks.